Educational Department Web Site for Libya Embassy, Malaysia - Sharif, Mohamed Elhadi M (2009)
The educational department of the Libyan embassy in Malaysia website playing major rule in different fields that explore and become important economic,commerce, military, health, education, diplomatic Etc.On the other hand many embassies in several countries facing difficulties in accessing organizing and collecting the data related to students specifically the register student in education department of the Libyan embassy in Malaysia, So I studied design website the educational department Libyan embassy in Malaysia,and is interested in opening a file for the student follow-up to the most important news of the educational department, to insert some data, File Number, Student Name, Libyan Address, Phone Number, Support Direction, Current Institution,Scientific Grade, Major, Start Study, End Study, Malaysian Address and Mail's Student,, also if there is any problem in the area of study a student can send a message to the educational department website or the consulted educational department e-mail for the consideration and resolution as soon as possible.